Development, growth and decline in Europe: New patterns of economic convergence and divergence? - Andreas P. Cornett; Nils Karl Soerensen (European Regional Science Association (ERSA), 2013)
The influence of general economic and fiscal policy is in recent years more significant than ever. Tight budgets sets limits on public spending in general and on regional development in particular, both with regard to programs specifically targeted on regional issue, but often also indirect due to changes in the geographical distribution of public spending (i.e. local purchasing of goods and services) or the location of institutions etc. Furthermore the focus on (global) competitiveness, innovation ?smart growth? in the Lisbon and Euro 2020 strategy seems to have a build in effect toward economic activities usually located in center or metropolitan areas. Based on an analysis of the dominant policy measures used in EU structural and R&D policy the aim of the current paper is to assess, to what extent they have supported regional convergence, not only between but also within countries. The conceptual point of departure is new economic growth theory and the measures derived from these concepts. An attempt is made to analyze regional difference in the relevant factor endowments and to measure the impacts on regional convergence in a European (country wise) and urban-rural perspective. The first part of the paper discusses the overall development with regard to Structural funds and the distribution of grants with focus on the developments and perspectives until 2020. The second part considers the impact on the process of convergence of the current decline in the overall economic trends in Europe in a regional context. In addition, in influence of innovation on the development in a European perspective in analyzed along with increasing concentration of the population in urban areas. Finally, the paper addresses the perspectives of the pursued policy in different regions.
Keywords: R11; R12; R58; 330; Recession; regional economic growth; convergence & divergence; EU structural policy; innovation